2000
DOI: 10.1006/viro.2000.0584
|View full text |Cite
|
Sign up to set email alerts
|

The Human Papillomavirus E7 Protein Is Able to Inhibit the Antiviral and Anti-growth Functions of Interferon-α

Abstract: It is now well recognized that cervical cancer is caused by infection with certain human papillomavirus (HPV) subtypes and while interferon-alpha (IFN-alpha) is used to treat HPV-infected lesions, HPV appears to have developed a means to avoid the effects of IFN-alpha. Clinically, resistance appears to be associated with the expression of the E7 oncoprotein. Here we investigated the effects of expression in cells of the E7 protein from high- and low-risk papillomavirus subtypes on a range of responses to IFN-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 24 publications
1
77
0
Order By: Relevance
“…Several in vitro studies demonstrated the ability of HPV oncoproteins to control signalling pathways that lead to the expression of IFNs and IFN-inducible genes (Barnard et al, 2000;Koromilas et al, 2001;O'Brien & Saveria Campo, 2002). Expression of HPV16 E6 in human keratinocytes was able to diminish the induction of IFN-b gene expression by Sendai virus and, consequently, the expression of IFN-inducible genes (Ronco et al, 1998).…”
mentioning
confidence: 99%
“…Several in vitro studies demonstrated the ability of HPV oncoproteins to control signalling pathways that lead to the expression of IFNs and IFN-inducible genes (Barnard et al, 2000;Koromilas et al, 2001;O'Brien & Saveria Campo, 2002). Expression of HPV16 E6 in human keratinocytes was able to diminish the induction of IFN-b gene expression by Sendai virus and, consequently, the expression of IFN-inducible genes (Ronco et al, 1998).…”
mentioning
confidence: 99%
“…For example, expression of HPV E6 and E7 protein prevents the immunoregulatory effects of IFN-a-and IFN-b-mediated antiviral responses. 20 It is furthermore observed that women with cervical cancer develop poor levels of E7-specific CTLs in response to the developing tumor 5,6 or to an E7 vaccine. 21 This poor cellular immune response may be caused by the expression of E7 in epithelial cells lacking costimulation, which may lead not only to immunosuppression but also to immunological tolerance.…”
mentioning
confidence: 99%
“…Both E6 and E7 oncoproteins inhibit IL-18-induced IFN-in natural killer (NK) cells [63]. Additionally the E7 oncoprotein arrests the antiviral signaling mediated by interferon-alpha (IFN-) [64,65] and has also been observed to inhibit the IRF-1-mediated activation of the IFN-promoter [66].…”
Section: Humoral Immune Responses and Cell-mediated Immune Responses mentioning
confidence: 99%